2014
DOI: 10.1371/journal.pone.0114331
|View full text |Cite
|
Sign up to set email alerts
|

Necessity and Effect of Combating Legionella pneumophila in Municipal Shower Systems

Abstract: The objective was to obtain research-based, holistic knowledge about necessity and effect of practiced measures against L. pneumophila in municipal shower systems in Stavanger, Norway. The effects of hot water treatment and membrane-filtering were investigated and compared to no intervention at all. The studies were done under real-world conditions. Additionally, a surveillance pilot study of municipal showers in Stavanger was performed. The validity of high total plate count (TPC) as an indication of L. pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 59 publications
2
16
0
1
Order By: Relevance
“…We apologize for not having mentioned this paper, but our Legionella data range in water samples agrees with results reported by Wiik et al [4]; that is, viable air-borne Legionella was infrequently detected at low concentrations in water samples.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…We apologize for not having mentioned this paper, but our Legionella data range in water samples agrees with results reported by Wiik et al [4]; that is, viable air-borne Legionella was infrequently detected at low concentrations in water samples.…”
supporting
confidence: 91%
“…The article of Wiik et al [4] reports that a high concentration of Legionella (>300,000 cfu/L) in water is required to detect Legionella in the air. We apologize for not having mentioned this paper, but our Legionella data range in water samples agrees with results reported by Wiik et al [4]; that is, viable air-borne Legionella was infrequently detected at low concentrations in water samples.…”
mentioning
confidence: 99%
“…In 2018, a study was published in kindergartens, schools, sports buildings, office buildings and nursing homes in Norway regarding the assessment of the use of various methods, among others thermal disinfection and membrane filtration in the fight against Legionella pneumophila in urban shower systems. Active surveillance did not show a significant effect of the methods assessed and no significant positive correlation was found between the total heterotrophic number of platelets (heterotrophic bacteria index) and Legionella pneumophila concentration, and the risk of Legionella infection is assessed as low and uncertain (24). As part of the European Center for Disease Prevention and Control (ECDC), there is the European Legionnaires' Disease Surveillance Network (ELDSNet), whose role is to detect, control and prevention of individual cases, group infections and outbreaks of legionnaires' disease in EU / EEA countries, as well as assistance in other countries to this extent.…”
Section: Discussionmentioning
confidence: 93%
“…dezynfekcji termicznej i filtracji membranowej w zwalczaniu Legionella pneumophila w miejskich systemach prysznicowych. Aktywny nadzór nie wykazał istotnego wpływu ocenianych metod oraz nie stwierdzono istotnej dodatniej korelacji między stężeniem całkowitej heterotroficznej liczby płytek (wskaźnik obecności bakterii heterotroficznych) a stężeniem Legionella pneumophila, a ryzyko zakażenia pałeczkami Legionella ocenia się jako niskie i niepewne (24). W ramach Europejskiego Centrum ds.…”
Section: Discussionunclassified
“…Legionella present in puddles on roads could be aerosolized by splashing or by wind. Recently, several studies have attempted to detect Legionella species in aerosols released from hot tap water in bathrooms, shower water, and compost [12][13][14]. These studies revealed that Legionella species were present in the aerosols derived from these environments.…”
Section: Introductionmentioning
confidence: 99%